Investigating English speaking skill problems encountered by students at Islamic modern boarding schools - Misna Amelia; Endang Komariah (Universitas Syiah Kuala, 2017)
This research is intended to analyze English speaking skill problems encountered by students. The sample of this research was 26 students from XI-MIA 1 class who have learned English for five years. They were chosen purposively. The data of this research were collected through speaking test and interview. The interview was conducted to see the students who got very low score from the speaking test. The findings from the speaking test showed that the students faced the problems in five aspect of speaking skill; pronunciation, grammar, fluency, comprehension, and vocabulary. The most dominant problems are pronunciation, grammar and fluency. The findings from the interview showed that the students they faced many problems such as inhibition, nothing to say, law participation and mother tongue used. To conclude, the students of Babun Najah Islamic Modern Boarding School faced the problems in speaking.